MORPHOLOGY OF SUPRA-SCAPULAR NOTCH AND ITS CLINICAL IMPORTANCE - Sajjad Jafar; Bindu Singh; Vipin Kumar; Shalini Gupta (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objectives: The suprascapular notch is placed at the upper border of the scapula. The anatomical variant of the notch is taken into consideration as one of the reasons of suprascapular nerve entrapment. In the existing study, we attempted to assess the morphology of the suprascapular notch of Indian human dry scapulae that is important to recognize and deal with specific reasons of suprascapular nerve entrapment, which might be beneficial to keep away from induced nerve lesion at some stage in open arthroscopic surgical procedures and assist in designing implants for the shoulder joint. Methods:This is an observational study, with a complete of one hundred fifty human dry scapulae being observed, tested and studied in detail. The kind of suprascapular notch become cited as according to the outline given with the aid of using Rengachary et al. Results: In the present study, on the basis of anatomical variations five types of suprascapular notches had been observed: type I, (9.21%); type II (21.%); type III (31.57%); type IV (17.10%); and type V (21%). type III notch become greater prevalent. Conclusion: The knowledge of suprascapular notch could be very useful withinside the prognosis and control of instances with shoulder ache because of suprascapular nerve entrapment and additionally whilst administering suprascapular nerve blocks for surgical procedures related to the shoulder region.